Preferensi dalam Memilih Hunian Menapak dan Vertikal oleh Generasi Y dan Z di Indonesia - Tang, Angel; Kusuma, Hanson E.; Riska, Annisa Safira (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2022)
The need for housing becomes important, especially for generations Y and Z who are dominating the world's population today. The type of dwelling itself is divided into tread dwelling and vertical dwelling. In determining the type of residence they want, someone always relates it to the criteria they want as well as generations Y and Z. This study aims to determine the preferences of generations Y and Z for the type of tread or vertical residence they want. The research uses a grounded theory approach with qualitative-exploratory methods. Data collection uses a questionnaire that is distributed online and is open-ended from a freely selected sample. The findings show that there are two types of housing that are possible for generations Y and Z, namely residential treads on the outskirts of the city and vertical housing in the city center. The reasons for choosing a residence on the outskirts of the city are: flexibility, convenience, value, environment, livable culture, and security. The reasons for choosing vertical housing in the city center are: location and accessibility, facilities, practicality, atmosphere, and compulsion.